2021
DOI: 10.1099/mgen.0.000560
|View full text |Cite
|
Sign up to set email alerts
|

Niche-specific adaptation of Lactobacillus helveticus strains isolated from malt whisky and dairy fermentations

Abstract: Lactobacillus helveticus is a well characterized lactobacillus for dairy fermentations that is also found in malt whisky fermentations. The two environments contain considerable differences related to microbial growth, including the presence of different growth inhibitors and nutrients. The present study characterized L. helveticus strains originating from dairy fermentations (called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In another study, supplementation of Lactobacillus species to chick embryos was shown to enhance cellular proliferation and increase the weight of lymphoid organs, including the spleen, thymus, and bursa of Fabricius, suggesting a possible role for probiotics in modulating the development of these lymphoid organs ( Madej et al, 2015 ). It is important to emphasize that probiotic lactobacilli isolated and reinoculated into the same host species (i.e., species-specific lactobacilli) demonstrated greater effectiveness compared to those isolated from different species ( La Reau et al, 2016 ; Kido et al, 2021 , Moeller et al, 2019 ). However, although much research focused on the effects of in ovo -delivered probiotics on immune responses and cellular and morphological changes in lymphoid organs of hatched chicks, there remains no clear evidence of whether lactobacilli influence the development and functional maturation of these organs in pre-hatched chicks at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, supplementation of Lactobacillus species to chick embryos was shown to enhance cellular proliferation and increase the weight of lymphoid organs, including the spleen, thymus, and bursa of Fabricius, suggesting a possible role for probiotics in modulating the development of these lymphoid organs ( Madej et al, 2015 ). It is important to emphasize that probiotic lactobacilli isolated and reinoculated into the same host species (i.e., species-specific lactobacilli) demonstrated greater effectiveness compared to those isolated from different species ( La Reau et al, 2016 ; Kido et al, 2021 , Moeller et al, 2019 ). However, although much research focused on the effects of in ovo -delivered probiotics on immune responses and cellular and morphological changes in lymphoid organs of hatched chicks, there remains no clear evidence of whether lactobacilli influence the development and functional maturation of these organs in pre-hatched chicks at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…In our view, to develop and select an effective probiotic consortium, it is important to use isolates that have been adapted to the host of interest, i.e., host-adapted (or species/specific) probiotic organisms. 13,14 The goal of this study is to isolate equine-specific lactobacilli from American Quarter horses at different stages of development and characterize their biochemical and genetic traits that allow them to survive and persist in the host. The American Quarter horses are the most popular breed in the United States of America (USA).…”
Section: Introductionmentioning
confidence: 99%
“…However, in their study, Limon et al used M. restricta MYA-4611, synonymous with the M. restricta type strain CBS 7877, which may not properly represent the fungus within the gut environment because it was originally isolated from the human skin and not from the human gut 27 . In general, niche-specific metabolic adaptation, which is normally linked to genomic variations and niche-dependent gene expression, is a well-established phenomenon, particularly in bacteria, based on phenotypic and multiomics analysis [28][29][30] . Fungi also reside in various environments, including different niches within the human host, and multiple selective pressures, such as oxygen depletion, nutrient limitation, and pH fluctuation, lead to niche-specific adaptation 31,32 .…”
Section: Introductionmentioning
confidence: 99%